2003
DOI: 10.1002/cne.10630
|View full text |Cite
|
Sign up to set email alerts
|

“Dormant basket cell” hypothesis revisited: Relative vulnerabilities of dentate gyrus mossy cells and inhibitory interneurons after hippocampal status epilepticus in the rat

Abstract: The "dormant basket cell" hypothesis suggests that postinjury hippocampal network hyperexcitability results from the loss of vulnerable neurons that normally excite insult-resistant inhibitory basket cells. We have reexamined the experimental basis of this hypothesis in light of reports that excitatory hilar mossy cells are not consistently vulnerable and inhibitory basket cells are not consistently seizure resistant. Prolonged afferent stimulation that reliably evoked granule cell discharges always produced e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
175
3
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(209 citation statements)
references
References 156 publications
(335 reference statements)
20
175
3
3
Order By: Relevance
“…In addition, NPY-IR interneurons are evidently lost in the hilus of the dentate gyrus but preserved in the granule cell layer in electrical stimulation-induced epilepsy [51] . Similar losses of NPY-IR interneurons have been reported in KA models [55] .…”
Section: Neuropeptide-containing Interneurons and Epilepsysupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, NPY-IR interneurons are evidently lost in the hilus of the dentate gyrus but preserved in the granule cell layer in electrical stimulation-induced epilepsy [51] . Similar losses of NPY-IR interneurons have been reported in KA models [55] .…”
Section: Neuropeptide-containing Interneurons and Epilepsysupporting
confidence: 84%
“…SE exhibits seizure activity persisting for a sufficient length of time [72] . SE leads to the loss and structural reorganization of interneurons and weake ned excitatory inputs to inhibitory interneurons [55,73] . In other types of epilepsy, including complex partial epilepsy, myoclonic epilepsy, and generalized tonic clonic seizures, interneurons exhibit similar characteristics.…”
Section: Interneurons In Various Types Of Epilepsymentioning
confidence: 99%
“…Such a mechanism has been reported in the hippocampus and EC layers II/III (Bekenstein and Lothman, 1993;Williams et al, 1993;Sloviter, 1987;Doherty and Dingledine, 2001;Sloviter et al, 2003;Kumar and Buckmaster, 2006). Experiments performed in pilocarpine-treated rats have also demonstrated that pharmacologically isolated, GABA A receptor-mediated IPSPs have more positive reversal potentials in neurons recorded in vitro from the epileptic subiculum, peirhinal cortex and amygdala (de Guzman et al, 2006;Benini and Avoli, 2005;Benini et al, 2011); these data often correlated with reduced levels of mRNA expression and immunoreactivity of the neuron-specific cotransporter KCC2.…”
Section: Gaba a Receptor-mediated Inhibition In Temporal Lobe Epilepsymentioning
confidence: 65%
“…Numerous studies indicate that the dentate gyrus is frequently involved in the generation of epileptic seizures (Heinemann et al, 1992;Lothman et al, 1992) and may exhibit characteristic histochemical and histopathologic changes, including changes in NPY expression (Sloviter, 1983(Sloviter, , 1991Sloviter et al, 2003). NPY expression was found markedly increased in hilar GABAergic interneurons, granule cells and sprouted mossy fibers (Bellmann et al, 1991;Chafetz et al, 1995;Lurton and Cavalheiro, 1997;Scharfman et al, 1999Scharfman et al, , 2002Sperk et al, 1992;Takahashi et al, 2000;Vezzani et al, 1996).…”
Section: Discussionmentioning
confidence: 99%